A Bottom-up Trend in Research of Management of Technology - Ishino, Yoko (School of Business and Management Institut Teknologi Bandung, 2014)
Management of Technology (MOT) is defined as an academic discipline of management that enables organizations to manage their technological fundamentals to create competitive advantage. MOT covers a wide range of contents including administrative strategy, R&D management, manufacturing management, technology transfer, production control, marketing, accounting, finance, business ethics, and others. For each topic, researchers have conducted their MOT research at various levels. However, a practical and pragmatic side of MOT surely affects its research trends. Finding changes of MOT research trends, or the chronological transitions of principal subjects, can help understand the key concepts of current MOT. This paper studied a bottom-up trend in research fields in MOT by applying a text-mining method to the conference proceedings of IAMOT (International Association for Management of Technology). First, focusing on only nouns found several keywords, which more frequently emerge over time in the IAMOT proceedings. Then, expanding the scope into other parts of speech viewed the keywords in a natural context. Finally, it was found that the use of an important keyword has qualitatively and quantitatively extended over time. In conclusion, a bottom-up trend in MOT research was detected and the effects of the social situation on the trend were discussed.Keywords: Management of Technology; Text Mining; Research Trend; Bottom-up Trend; Patent